Performance of wire-EDM parameters on machining characteristics of titanium alloy (Ti6Al4V) using Taguchi method - Md Ali, Mohd Amran; Raja Abdullah, Raja Izamshah; Hussein, Nur Izan Syahriah; Kasim, Mohd Shahir; Sulaiman, Mohd Amri; Salleh, Mohd Rizal; Mohamad, Effendi; Subramonian, Sivarao; Liew, Pay Jun; Abdullah, Zulkeflee (2014)
The effect of wire electrical discharge machining (wire-EDM) parameters on machining characteristics of Titanium Alloy (Ti6Al4V) is studied. 0.2mm diameter of electrolytic brass wire having composition ratio Copper and Zinc 60:40 was selected as wire electrode. The experiment was done using SODICK VZ500L wire-EDM machine. Orthogonal arrays design of Taguchi method was applied to design the experimental matrix and the data was analyzed using analysis of variance (ANOVA). It is found that the most significant parameter affected material removal rate (MRR) is servo voltage followed by pulse duration, while pulse interval shows the less significant factor. The validation of optimum parameter has been done for MRR and it is found that after optimization process, the MRR can reach up to 0.044g/min, which is a 4.76% increased as compared to maximum MRR result from initial experiment. Surface roughness (RA) reduces to 4.35% meanwhile kerf width (Kw) slightly increases to 0.036% after conformation run of the optimization combination process parameters. Pulse duration of input parameter of gives the most significant impact to RA and Kw. Thus, it shows that the results of wire-EDM on Ti6Al4V are particularly useful for industrial practitioners and researchers to determine the best combination of parameters which lead to optimize the machining performance.